DETERMINANTS OF VOTERS` BEHAVIOR AND VOTING INTENTION IN GHANA; MEDIATING AND MODERATING ROLE OF VOTERS` TRUST AND VOLTERS` LOYALTY RESPECTIVELY - Zakari Bukari; Abu Bakar Abdul Hamid; Hishamuddin Md.Som (Journal of International Conference Proceedings (JICP), 2019)
Voters` participation and intention is considered fundamental in an electoral process, as it has consequences on political party`s performance and strengthening of a democratic state. Yet almost half the countries in the world have voter turnouts of (60–79) % whilst only 20% of the countries have voter turnout above 80%. The average turnout trend in Ghana for the past 24 years is 64.34%. When a significant large proportion of the voting population shows apathetic attitudes towards the process that enable participation of the public in democracy, it questions the extent to which our democracy can be consolidated. To be able to predict and influences voters` behavior, political parties and political consultants need to identified determinants of voters` behavior. Given the importance that democratic societies placed on citizens’ participation in the democratic process. Incorporating their views, opinions and feelings on voters` behavior determinants factors such as; political issues, contingency situations, political candidates personality, Epistemic value, Trust for a party candidates as well as loyalty to a party on their intention to participate in presidential election and their choice of a party and candidate will offers an empirical dimension to the evaluation of our democratic consolidation and also help the leadership of the various political parties in Ghana in their quest to develop appropriate strategies with the so aim of winning election. Utilizing a predictive model of voters` behavior, this study is pursued to identify; the theories, models and motivation behind a sample of voters who cast a ballot in the 2012 and 2016 presidential election. Pairwise discriminant analysis and structural equation model are used to identify the motivation behind the choice behavior of voters at both candidate and party level. The objectives of this is to conceptualized a strategic direction practices and propose a theoretical framework of voters` behavior determinants, that can help effectively and efficiently predict voters` participation and intention and also to determine the extent to which western scholarly explanation of voters` behavior can be applied to Ghanaians voters` behavior.